2018
DOI: 10.4258/hir.2018.24.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mobile Health Application Use to Improve Health Behavior Changes: A Systematic Review of Randomized Controlled Trials

Abstract: ObjectivesThe purpose of this study was to examine the effectiveness of mobile health applications in changing health-related behaviors and clinical health outcomes.MethodsA systematic review was conducted in this study. We conducted a comprehensive bibliographic search of articles on health behavior changes related to the use of mobile health applications in peer-reviewed journals published between January 1, 2000 and May 31, 2017. We used databases including CHINAHL, Ovid-Medline, EMBASE, and PubMed. The ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
116
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(128 citation statements)
references
References 29 publications
3
116
1
8
Order By: Relevance
“…In a systematic review, mHealth apps use were found to have a positive impact on health related behaviors and clinical outcomes. The users of mHealth apps reported more satisfaction in comparison to the conventional care . A rapid evidence review of mobile apps in the self‐management of diabetes has concluded that use of commercially available mobile health apps when used with an additional support from healthcare provider improved the short‐term diabetes related outcomes.…”
mentioning
confidence: 99%
“…In a systematic review, mHealth apps use were found to have a positive impact on health related behaviors and clinical outcomes. The users of mHealth apps reported more satisfaction in comparison to the conventional care . A rapid evidence review of mobile apps in the self‐management of diabetes has concluded that use of commercially available mobile health apps when used with an additional support from healthcare provider improved the short‐term diabetes related outcomes.…”
mentioning
confidence: 99%
“…Chow et al [ 7 ] reported that, due to the recent increase in the number of smartphone users, smartphone applications have become an important tool in disease management. Accordingly, mHealth and cardiac telerehabilitation have been established as a new form of disease management and have advanced greatly [ 9 15 ]. Varnfield et al [ 19 ] reported that, since applications can be easily built into smartphones, cardiac patients can use them at any time or place, and as a result, these applications can be effective tools for realizing mobile education and health management.…”
Section: Discussionmentioning
confidence: 99%
“…Personalized care based on the characteristics of the individual has become possible, thereby enhancing the efficiency of such services [ 14 ]. Moreover, by enabling communication between providers and patients regardless of spatio-temporal limitations, more people can provide necessary care, leading to higher satisfaction than that for conventional interventions [ 15 ]. Recently, using monitoring sensors and sending feedback to providers and patients has provided new areas of treatment and development.…”
Section: Introductionmentioning
confidence: 99%
“…Milne-Ives and colleagues [ 12 ] systematically reviewed 52 RCT studies and found no strong evidence for the effectiveness of mobile apps because few studies found significant differences between the app and control groups. Han and Lee [ 13 ] found that the use of mobile health applications has a positive impact on health-related behaviors and clinical health outcomes.…”
Section: Introductionmentioning
confidence: 99%